2005
DOI: 10.1212/01.wnl.0000163771.96962.1f
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug use of women with epilepsy and congenital malformations in offspring

Abstract: Excess risk was confined to patients using valproate during pregnancy. The risk for malformations was not elevated in offspring of mothers using carbamazepine, oxcarbazepine, or phenytoin (as monotherapy or polytherapy without valproate).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
174
4
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(190 citation statements)
references
References 25 publications
5
174
4
7
Order By: Relevance
“…16 A study using the Finnish National Medical Birth Registry examined 2,350 births in women with epilepsy and showed an increase risk of malformations for VPA compared with nonexposed and children exposed in utero to other AEDs; the rate of malformations for VPA monotherapy was 10.7%. 17 The United Kingdom Pregnancy Registry, which included 3,607 pregnancies, found a malformation rate of 6.2% for VPA monotherapy, which was significantly greater than CBZ (2.2%). 18 Four other prospective studies all exhibited a trend toward higher malformations for VPA despite their relatively low power.…”
Section: Discussionmentioning
confidence: 99%
“…16 A study using the Finnish National Medical Birth Registry examined 2,350 births in women with epilepsy and showed an increase risk of malformations for VPA compared with nonexposed and children exposed in utero to other AEDs; the rate of malformations for VPA monotherapy was 10.7%. 17 The United Kingdom Pregnancy Registry, which included 3,607 pregnancies, found a malformation rate of 6.2% for VPA monotherapy, which was significantly greater than CBZ (2.2%). 18 Four other prospective studies all exhibited a trend toward higher malformations for VPA despite their relatively low power.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest that NSCLP results from the complex interaction of both genes and environmental factors. Folic acid deficiency, maternal smoking and anticonvulsant medications are some of the environmental influences that have been associated with NSCLP (3)(4)(5). Evidence for involvement of genes in NSCLP comes from family studies which show that: (1) the heritability of NSCLP in a Caucasian population is approximately 76%, (2) the rate of concordance is higher in monozygotic (25-40%) than dizygotic (3-6%) twins and (3) there is an increased relative risk to siblings (λ s = 30-40) compared to the general population (1,6).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the teratogenicity of PHT has been established amongst clinicians and basic scientists for almost 40 years. As is often the case, some studies found significant associations between in utero PHT exposure and MCMs [Kaneko et al, 1999;Vajda et al, 2006;Wide et al, 2004], while others failed to find such associations [Artama et al, 2005;Morrow et al, 2006;Vajda et al, 2007Vajda et al, , 2012 (Table II).…”
Section: Antiepileptic Drugsmentioning
confidence: 82%